"Frame Up" by Angela Davis, 1972 - Davis, Angela::::::::::::::: (San Francisco, CA; National United Committee to Free Angela Davis and All Political Prisoners; United States, 2024)
"Frame Up: The Opening Defense Statement Made by Angela Y. Davis, March 29, 1972." Pamphlet published by the National United Committee to Free Angela Davis, containing the opening defense statement made by Davis in the Santa Clara County, California Superior Court on March 29, 1972, during her trial for charges of murder, kidnapping, and conspiracy. The pamphlet was part of efforts to garner support for her acquittal and raise awareness of the political nature of her prosecution.